A Threonine‐Forming Oxazetidine Amino Acid for the Chemical Synthesis of Proteins through KAHA Ligation. Issue 36 (24th July 2019) - Baldauf, Simon; Schauenburg, Dominik; Bode, Jeffrey W.
Abstract: α‐Ketoacid‐hydroxylamine (KAHA) ligation allows the coupling of unprotected peptide segments through the chemoselective formation of an amide bond. Currently, the most widely used variant employs a 5‐membered cyclic hydroxylamine that forms a homoserine ester as the primary ligation product. In order to directly form amide‐linked threonine residues at the ligation site, we prepared a new 4‐membered cyclic hydroxylamine building block. This monomer was applied to the synthesis of wild‐type ubiquitin‐conjugating enzyme UbcH5a (146 residues) and Titin protein domain TI I27 (89 residues). Both the resulting UbcH5a and the variant with two homoserine residues showed identical activity to a recombinant variant in a ubiquitination assay. Abstract : Thr(ee) from four : An oxazetidine amino acid enables direct formation of amide‐linked threonine residues at the ligation site in KAHA ligations of unprotected peptide segments. This 4‐membered cyclic hydroxylamine building block was applied to the synthesis of E2 ubiquitin‐conjugating enzyme UbcH5a and Titin domain TI I27. The obtained UbcH5a showed identical activity to a recombinant variant in a ubiquitination assay.